Dietary modulation of the inflammatory cascade. (February 2014) - Dawson, Dolphus R.; Branch‐Mays, Grishondra; Gonzalez, Octavio A.; Ebersole, Jeffrey L.
Abstract: Dietary supplementation has traditionally consisted of adding vitamins and/or minerals to correct or prevent a nutritional deficiency. When supplementing the diet with other inflammatory mediators, such as essential fatty acids, there is an adjunctive benefit to the standard therapies used in the control of chronic inflammatory diseases such as Crohn's disease or rheumatoid arthritis. This review focuses on the strategies utilized for therapeutic modulation of the inflammatory cascade through dietary supplementation with specific biomolecules. Examples of how these biomolecules affect local and systemic immune responses to chronic inflammation are examined. In particular, an overview of the literature identifying the potential to modify the host response to chronic periodontitis is provided.